The Influence of Gender and Hope on the Resilience of Bullied Adolescents - Nur Setiawati Dewi; Megah Andriany; Ovi Imrotul Lathifah; Artika Nurrahima; Rita Hadi Widyastuti; Nurullya Rachma; Elis Hartati (Jurnal Keperawatan Indonesia, 2023)
Bullying is currently a national concern in Indonesia. Many of the country’s children and adolescents have taken their lives due to a lack of resilience in the face of bullying. However, some studies have revealed that victims can survive the adverse effects of bullying. This study aimed to analyze the roles of hope and sociodemographic characteristics in the resilience of bullied adolescents in Indonesia. The study used a cross-sectional design and selected 305 bullied high school students in Semarang as participants through purposive sampling. The Adolescent Resilience Scale and the Children’s Hope Scale were used to measure the participants’ resilience and hope. A multiple linear regression test was applied to analyze the influence of hope and sociodemographic characteristics on resilience. The results showed that gender (β = -0.149, p = 0.001) and hope (β = 0.571, p = 0.001) significantly influenced the resilience of the bullied adolescents. Working through schools’ health units, nurses should establish partnerships with stakeholders, such as school personnel and parents, to develop hope-based intervention programs aimed at enhancing the resilience of bullied adolescents. Abstrak Pengaruh Gender dan Harapan terhadap Resiliensi Remaja Korban Perundungan. Fenomena perundungan di Indonesia saat ini telah menjadi perhatian nasional. Banyak anak dan remaja yang bunuh diri karena tidak kuat menghadapi perundungan. Namun, penelitian mengungkapkan bahwa beberapa korban dapat bertahan dari dampak buruk perundungan. Penelitian ini bertujuan untuk menganalisis peran harapan dan karakteristik sosiodemografi terhadap resiliensi remaja korban perundungan di Indonesia. Penelitian ini merupakan penelitian cross-sectional dengan 305 siswa SMA korban perundungan di Kota Semarang terlibat sebagai responden yang dipilih melalui teknik purposive sampling. Kuesioner Adolescent Resilience Scale (ARS) dan Children's Hope Scale (CHS) digunakan untuk mengukur resiliensi dan harapan remaja korban perundungan. Uji regresi linier berganda digunakan untuk menganalisis pengaruh harapan dan karakteristik sosiodemografi terhadap resiliensi atau ketahanan. Hasil penelitian menunjukkan jenis kelamin (β = -0.149, p = 0.001) dan harapan (β = 0.571, p = 0.001) secara signifikan mempengaruhi resiliensi remaja korban perundungan. Perawat, melalui Unit Kesehatan Sekolah (UKS), perlu menjalin kemitraan dengan pemangku kepentingan seperti guru di sekolah dan para orang tua, guna mengembangkan program intervensi berbasis harapan yang bertujuan untuk meningkatkan resiliensi remaja korban perundungan. Kata Kunci: harapan, perundungan, remaja, resiliensi